PRAKTIK ADAT KAWIN TANGKAP MASYARAKAT SUMBA SEBAGAI BENTUK NYATA KEKERASAN SEKSUAL - Juliani, Wenny; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: Bride-napping in the Sumba community is one of the traditional practices that continue to be carried out and preserved to this day. Ideally, bride-napping holds profound and noble philosophical values when performed per established norms and customs. However, in reality, this tradition is often misunderstood and irresponsibly conducted, turning it into a criminal act of sexual violence against women who become victims of misinterpreted bride-napping practices. This paper aims to examine and elaborate on how a tradition of high noble value can transform into a criminal act when carried out contrary to customary norms. The method used in this study is normative descriptive, sourced from library research. Ultimately, all cultures and traditions in society deserve our respect and appreciation to ensure their preservation as part of the nation's identity. However, no tradition or culture should cause harm or disruption within the community. The Sexual Violence Crimes Act (UU Tindak Pidana Kekerasan Seksual) is one of the legal frameworks that can serve as a foundation and motivation to continue advocating for the rights and freedom of women, particularly for women in Sumba who fall victim to irresponsible and norm-violating bride-napping practices.Keywords: Customary Law, Bride-Napping, Sumbanese, Sexual Violance